Knowledge gaps and national research priorities for COVID-19 in Iran - Bahareh Yazdizadeh; Elham Ehsani-Chimeh; Kazem Zendehdel; Mohammadreza Mobinizadeh; Bita Mesgarpour; Zeinab Fakoorfard (BMC, 2022)
Abstract Background In the present COVID-19 crisis, one of the greatest challenges for research funding at both the international and national level is selecting the best research topic to achieve efficiency and equity in health research and to address the knowledge gap urgently raised due to the event. Despite international recommendations, countries should consider their context-specific situation and define local research priorities. We aimed to exercise a priority-setting activity to identify the knowledge gaps and suggest research priorities in response to the COVID-19 epidemic in Iran. Methods First, we tried to identify the contextual knowledge gaps based on an online survey, performing key informant interviews (i.e. health professionals, policy-makers and managers) and media analysis. We also performed a literature review and considered international research priorities for COVID-19. Subsequently, we prepared a list of research questions and challenges to respond to the COVID-19 crisis in Iran using a systems approach. Then we mapped approved COVID-19 research projects in the country to research questions. Finally, we compared the identified research questions (not challenges) with the prioritized research from international organizations and then prioritized them for Iran. Results We found risk factors and epidemiological dissemination patterns of the virus and its consequences in an epidemiology domain, implementation of clinical and hygiene in a clinical management domain, genetic studies for targeting prevention and treatment in a candidate treatment and vaccine research and development (R&D) knowledge domain, examination of the manifestations of ethics in society instead of ethics in research in an ethics domain, "care, access and health system" and "public health and participation in response to public health and clinical research" as two sub-domains of a social sciences domain, and finally, no new questions in either the virology, transmission, diagnosis or animal and environmental domain. Conclusions In the event of global health crises like COVID-19, prioritization of research questions can be done globally, but some of the research priorities are context-specific and may vary by regional needs. To better manage research resources, researchers must respond to the challenges faced in each country based on its political, economic, social and cultural characteristics, and to make evidence-informed decisions, global knowledge gaps must be customized in each country.